2015
DOI: 10.1002/path.4554
|View full text |Cite
|
Sign up to set email alerts
|

Truncated HBx‐dependent silencing of GAS2 promotes hepatocarcinogenesis through deregulation of cell cycle, senescence and p53‐mediated apoptosis

Abstract: Hepatocellular carcinoma (HCC) is a worldwide threat to public health, especially in China, where chronic hepatitis B virus (HBV) infection is found in 80-90% of all HCCs. The HBV-encoded X antigen (HBx) is a trans-regulatory protein involved in virus-induced hepatocarcinogenesis. Although the carboxyl-terminus-truncated HBx, rather than the full-length counterpart, is frequently overexpressed in human HCCs, its functional mechanisms are not fully defined. We investigated the molecular function of a naturally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 46 publications
0
41
0
Order By: Relevance
“…Previous study demonstrated that some point mutations in HBx gene, such as the double substitution K130M and V131I, generated completely distinct impact on regulation of E-cadherin expression and cell migration [11]. In this study, we found that HBxΔ31, rather than full-length HBx, repressed Maspin, RhoGDIα and CAPZB expressions at transcription initial steps by inducing their promoter inactivation.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Previous study demonstrated that some point mutations in HBx gene, such as the double substitution K130M and V131I, generated completely distinct impact on regulation of E-cadherin expression and cell migration [11]. In this study, we found that HBxΔ31, rather than full-length HBx, repressed Maspin, RhoGDIα and CAPZB expressions at transcription initial steps by inducing their promoter inactivation.…”
Section: Discussionmentioning
confidence: 48%
“…These natural C-terminal truncated HBx (Ct-HBx), frequently expressed in HBV-associated HCCs, have been shown to abrogate the growth-suppressive effects induced by full-length HBx, increase the proliferation of neoplastic cell, and promote the transforming ability of hepatocytes [9–11]. Thus, Ct-HBx may play a important role in facilitating hepatocarcinogenesis via modifying biological functions of full-length HBx.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the gas2 gene is a caspase-3 substrate that is cleaved by caspase-3 and is involved in the morphological changes of apoptotic cells [13, 25], on the other overexpressing gas2 does not directly induce apoptosis but may increase sensitivity of cells to apoptotic signals [14]. Gas2 was shown to be a component of the microfilament network system [11, 26, 27], similarly, a network of Gas2 expression was identified in the cell cytoplasm in this study. Moreover, tissue distribution of Gas2 indicated that this gene was expressed ubiquitously, with the highest expression in the liver, indicating that liver might be one of the most important locations where Gas2 carry out physiological function.…”
Section: Discussionmentioning
confidence: 99%
“…In this line, HBx is able to override cellular senescence by suppression of cyclin-dependent kinase inhibitors INK4a (p16), as well as p21 (Cip1/CDKN1A) via promoter hypermethylation and repression of retinoblastoma protein [57]. Recently, a similar function, including deregulated cell growth and senescence was reported for a naturally occurring HBx variant, which has 35 amino acids deleted at the C-terminus (HBxDelta35) by direct silencing of the gene GAS2 (growth arrest-specific 2) [58]. A second mode of interference with cellular signaling pathways by HBx is that it can bind and inhibit the function of signal transducers or transcription factors, for example, wild-type p53 protein, thereby limiting p53-specific tumor suppressor functions [59,60].…”
Section: The Role Of Hbx In Hepatocellular Transformationmentioning
confidence: 95%